Research trends and hotspots of acupuncture for knee osteoarthritis from 2004 to 2024: a bibliometric analysis - Zhou, Jun; Zhang, Kuayue; Zhao, Fanying; Liu, Xueyan; Zhang, Jiarun; Yuan, Fang; Liu, Lu; Li, Bin (Frontiers in Medicine, 2025)
BackgroundKnee osteoarthritis (KOA) is a leading cause of pain and disability worldwide. Acupuncture has emerged as a prominent non-pharmacological treatment for KOA. This study aims to analyze the general research status, hotspots, and trends of acupuncture in the treatment of KOA.MethodsOn January 19, 2025, a comprehensive search was conducted in the Web of Science Core Collection (WoSCC) for all available literature related to acupuncture and KOA. VOSviewer and CiteSpace software were employed for bibliometric analysis.ResultsA total of 295 publications were retrieved, covering 26 countries, 133 institutions, and 107 journals, with contributions from 1,711 authors. Since 2015, the number of publications on acupuncture for KOA has seen a rapid increase, indicating growing global interest in acupuncture as a potential treatment for KOA. China contributed 73.56% of the research, followed by the United States (10.17%) and the United Kingdom (6.44%). China, the U.S., and the U.K. maintain close academic collaborations, especially between China and the U.S. Beijing University of Chinese Medicine published the most articles (53), but cross-institutional collaboration remains limited. The journal Medicine published the most papers, while Osteoarthritis and Cartilage was the most cited (470 times). Key researchers such as Jianfeng Tu (19 papers), Cunzhi Liu (17 papers), and Liqiong Wang (15 papers), focused on comparing electroacupuncture and traditional acupuncture for KOA. Brian M Berman, the most cited researcher (106 times), made significant contributions to electroacupuncture research. Keyword analysis revealed chronic pain, analgesia, randomized controlled trial (RCT), and meta-analysis as key themes, with electroacupuncture emerging as the current research hotspot.ConclusionWith the support of high-quality randomized controlled trial, acupuncture is increasingly recognized as an effective treatment for KOA. Future research should focus on standardizing treatment protocols and determining the optimal dosage and frequency of acupuncture to maximize clinical efficacy.